A Review on Fingerprint Recoginition Technique Using Real Minutia Identification (International Journal of Engineering and Computer Science, 2014)
Fingerprint matching is one of the most efficient and successful technique for human identification with easy to implement and get accurate results. This  paper  presents  a  review on study  and  implementation  of  a  fingerprint  recognition  system  based  on  Minutiae  based  matching quite  frequently  used  in  various  fingerprint  algorithms  and  techniques.  This approach mainly involves extraction of unique identification points called minutiae points from the captured fingerprint images and then performing fingerprint matching based on the number of minutiae pairings among two fingerprints in question. The spurious minutia are removed by identifying the false percept minutia at the extraction stage.